Analysis of the Relationship between Job Satisfaction and Employee Performance at the Sudiang Samsat Office, Makassar City - Cynthia Ayu Yulianto; Syahrir; Nur Apriyani (LP2M IAIN Palopo, 2025)
This study aims to analyze the relationship between job satisfaction and employee performance. This study uses a quantitative approach with an explanatory type. The study population was all 55 Samsat Sudiang employees who were also sampled through census techniques. Data collection was carried out through observation, interviews, and questionnaires. Data analysis techniques used Crosstab and Kendall's Rank. The results of the study indicate that there is a positive and significant relationship between job satisfaction and employee performance, with a Kendall's Tau correlation coefficient of 0.671 and a significance of 0.000. The Z test produced a value of 7.234 > 1.96, which strengthens the evidence of the significance of the relationship. The coefficient of determination of 45% indicates that job satisfaction contributes 45% to the variation in employee performance, while the other 55% is influenced by other external factors. This finding implies that efforts to improve employee performance need to be preceded by increasing job satisfaction through improvements in the compensation system, work environment, and relationships between superiors and subordinates. This study provides recommendations for strengthening internal policies based on welfare and developing employee capacity on an ongoing basis.